Quality attributes and composition of meat from red deer (Cervus elaphus), fallow deer (Dama dama) and Aberdeen Angus and Holstein cattle (Bos taurus) - Bureš, Daniel; Bartoň, Luděk; Kotrba, Radim; Hakl, Josef (Journal of the Science of Food and Agriculture, 2015)
BACKGROUND: The consumption of venison from deer species has increased in recent years owing to presumably positive health effects. Therefore a comparison was made of the physical characteristics, chemical composition and sensory attributes of meat obtained from red deer, fallow deer and Aberdeen Angus and Holstein cattle raised under conditions typical for commercial farming practice and slaughtered at similar ages. RESULTS: Venison had one-quarter the crude fat content, lower total collagen and a higher proportion of heat-soluble collagen. It was darker and less yellow than beef. Deer species provided meat with higher polyunsaturated/saturated fatty acid ratio and lower atherogenic index. In addition, the venison of red deer contained five times as much n-3 polyunsaturated fatty acids as the beef. Steaks prepared from venison were scored higher than beef for flavour and aroma intensity; they were also tenderer and more easily chewable. CONCLUSION: Compared with beef, venison from two widely farmed deer species was superior in nutrient composition, thus offering potential benefits for human consumption, and it received higher scores for most of the sensory attributes examined.
Keywords: Cattle; Odorants; Animals; skot; Fatty Acids, Omega-3; Fats; barva; Collagen; nutriční hodnota; lidé; maso; kolagen; Deer; Nutritive Value; Meat; Color; chuť; odoranty; mechanický stres; Stress, Mechanical; omega-3 mastné kyseliny; Atherosclerosis; Taste; ateroskleróza; tuky; zvířata; vysoká zvěř; Humans